Using Opivo “Origami Pinch of Vocabulary” as a Learning Media in Teaching Vocabulary of Seventh Grade Student in MTs Mu’allimin Muhammadiyah Yogyakarta - Erika Nurul Khakiki; Sri Wiyanah (JEdu: Journal of English Education, 2022)
This research was conducted because students lack in mastering English vocabulary. The data on the field shows that lack of vocabulary is caused by learning materials that are not quite interesting. Therefore, students have difficulty in learning and mastering the material. Since the problems in the field, the researcher tries to apply origami as learning media which attracts students in order to make the learning process interesting and appealing. This research aims to find out the effectiveness of using OPIVO as media learning in teaching vocabulary at seventh grade MTS Mualimin Muhammadiyah of Yogyakarta. The research was conducted at MTS Mu’allimin Muhammadiyah of Yogyakarta in the academic year 2019/2020. This research was an experimental research. This design used two groups, namely the experiment group and the control group, which were randomly chosen to consist of VIIB and VIIC. In this research, the experiment class was given treatment while the control class did not. The collected data used pre-test and post-test. Then, the analysis technique used by SPSS followed by a t-test. The result of the research concluded that using OPIVO as learning media was effective in teaching vocabulary. The t-test result t-count: 2845 and t-table: 1,71387, because Tcount> Ttable, so that the Ho was rejected.Therefore OPIVO (Origami Pinch of Vocabulary) as a learning media was effective to use in learning vocabulary. It can be seen from the data that post-test was better than pre-test. The mean of pre-test was 72.97 and the mean of post test was 77.43. The data shows significant increasing for improving vocabulary in MTS Muhammadiyah Mua’llimin Yogyakarta.